The discovery of the lymphatic system in the seventeenth century. Part V: an ode to the nerves. Issue 5 (3rd September 2019) - Suy, Raphael; Thomis, Sarah; Fourneau, Inge
Abstract: The English anatomists Francis Glisson and Thomas Wharton introduced theories on the use of recently discovered lymphatic system in the1650s. Their main idea was that membranous tissues were supplied by nerves with a vital fluid produced within nutritive glands, to be carried to the brain and thence from the brain to all membranous tissues, including glands. They stated that the distribution of the vital fluid was based on the similarity between its ingredients and the needs of the recipient tissues, and not on the weight, size or location of pores encountered, as maintained by Descartes. Lymph, a mixture of waste from the consumed vital fluid and moisture transuded by arterial capillaries, was absorbed by the lymphatic vessels to be excreted via excretory glands, or to be diverted to the venous system by reductive glands. The theories of Glisson and Wharton were very soon rejected to be replaced by a mechanistic philosophy, a legacy of Descartes' theories.